Spatial Planning and Sustainable Development of Qiangang Village Based on Catalyst Theory - Lin Xiuhong; Wu Yilin (E3S Web of Conferences)
In previous years, construction has proven that the development model of urbanization, large-scale demolition and construction, and pursuit of efficiency are not suitable for rural areas. We need to explore new ways that are more in line with rural development. Catalyst Theory is the process of generating catalytic reactions through small-scale element modification or introduction, driving the activation rate of surrounding large-scale spaces, and striving to create a spatial development model of “small leads to large” with minimal cost investment and minimal spatial intervention. Based on our team's field research data on Qiangang Village over the past six years, we have proposed the spatial planning concept of “Old Village - Catalyst” in Qiangang Village and constructed a planning framework for spatial catalyst, functional catalyst, and cultural catalyst. This article helps to fill the gap in the application of Catalyst Theory in rural planning practice and provides a guidance manual for the restoration and sustainable development of villages in Guangdong Province.